Pacific Economic Monitor December 2019.
The 2019 growth forecast for the Pacific subregion has been raised from 3.5% to 4.2%, driven mainly by higher liquefied natural gas production in Papua New Guinea and increased construction expenditure in Samoa and Solomon Islands, as well as lower than projected economic decline in Nauru. However, project delays in Papua New Guinea, tepid growth in some economies, and slower recovery in others will likely moderate subregional growth to 2.6% in 2020.
Keywords: Private sector; Renewable energy; Industry and state; Electronic books